Standardization of production technology for cucumber (Cucumis sativus L.) under protected environment (Indian Journal of Arid Horticulture, 2024)
An experiment was conducted to standardize the production technology for cucumber (Cucumis sativus L.) under protected cultivation at the Central Institute of Arid Horticulture, Bikaner, during the year 2010-11. The experiment was laid out in a Randomized Block Design with a factorial concept, comprising three environments, namely, glasshouse, polyhouse, and net house, and five varieties (Isatish, Hilton, Alamgir-CT-180, Poona Khira, Himangi) of cucumber. The results indicated a significant difference in all the vegetative growth parameters studied. The maximum vine length (3.01 m), number of leaves (24.53), number of branches (1.75), and leaf area (448.37 cm²) were found in the glasshouse. Among different varieties of cucumber, the maximum vine length (3.26 m), number of leaves (29.96), number of branches (1.73), and leaf area (449.71 cm²) were recorded in the variety Isatish. The protected structures significantly influenced photosynthetic rate (μm CO₂/m²/s), transpiration rate (μm H₂O/m²/s), and chlorophyll content (mg/g of fresh weight). The maximum photosynthetic rate (12.83 μm CO₂/m²/s) and chlorophyll content (1.30 mg/g) were found in the glasshouse. Maximum yield per hectare (84.06 t/ha) was recorded in the cucumber crop raised under glasshouse conditions. Among the varieties, maximum yield per hectare (86.78 t/ha) was recorded in the variety Isatish, whereas the minimum yield per hectare (59.01 t/ha) was recorded in the variety Himangi.
Keywords: Cucumber; Zero energy polyhouse; Net house; Glasshouse; Cultivars; Parthenocarpic